EDUCATING THE YOUNG GENERATION WITH TRADITIONS OF NATIONAL MUSIC (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article describes the historical processes of the art of maqom, which is our national music. The theoretical views of our thinkers and scientists on the art of national music are described.